The Effects of Vermicompost, Farm Manure, and DAP+Urea Fertilizers on Safflower (Carthamus tinctorius L.) Growth and Soil Enzyme Activity in Saline and Non-Saline Soils - Vedat BEYYAVAŞ; Suat CUN; Erdal SAKİN; Emrah RAMAZANOĞLU; Çiğdem KARACAN (ISPEC Journal of Agricultural Sciences)
Safflower (Carthamus tinctorius L.) is one of the oldest cultivated crops, known for its adaptability to extreme environmental conditions such as high temperatures, drought, and salinity. This study investigates the influence of vermicompost, farm manure, and DAP+Urea fertilizers on safflower growth and soil enzyme activity under saline and non-saline soil conditions. The findings reveal that vermicompost application significantly enhanced plant growth, whereas farm manure application contributed to more significant soil enzyme activity. Across both soil types, plant growth indicators—including plant height, root length, leaf count, leaf area, fresh and dry biomass, root fresh weight, and SPAD values exhibited notable improvements with these treatments. Soil enzyme activities increased by 68.37%, 41.07%, and 25.52% (urease, DHG, and CAT, respectively) in non-saline soil, while saline soil exhibited corresponding increases of 34.0%, 33.62%, and 25.71%. The study underscores the importance of farm manure in mitigating salinity stress and improving soil quality.